RADIOGRAPHIC COMPARATIVE REGENERATIVE EFFECTS OF HYALURONATE AND PIROXICAM IN OSTEOARTHRITIS MODELS OF RATS - Ishaq, Noaman; Batool, Saba; Qammar, Maria; Aziz, Muhammad Imran; Khan, Muhammad Waqar Aslam; Javaid, Sadia (Pakistan Journal of Physiology, 2022)
Background: Osteoarthritis is the most common degenerative joint disease that affects commonly in old age. Standard treatment of this disease is still underdeveloped, however multiple drug groups delay progression or reduce the symptoms. Objective of this study was to assess and compare the regenerative effects of hyaluronate and piroxicam in a rat model of osteoarthritis at the radiographic level. Methods: This laboratory-based randomized trial was conducted at Department of Pharmacology Army Medical College, Rawalpindi, from May to July 2019. Resection of the medial meniscus and anterior cruciate ligament resulted in osteoarthritis in the right knee joints of 24 rats. They were separated into 3 groups of 8 rats each. For 4 weeks, groups I, II, and III received intra-articular saline, hyaluronate, and piroxicam, respectively. After one week, radiographs of the anaesthetized rats’ matching knee joints were collected. Results: Comparison of radiograph of control group with drug treated group confirmed regenerative effects of hyaluronate and piroxicam (p=0.001). However comparison of hyaluronate and piroxicam treated groups had p=0.335 that professed both drug have equal regenerative effects in rat model of osteoarthritis. Conclusion: In a rat model of osteoarthritis, intra-articular injection of hyaluronate acid and piroxicam had regenerating benefits at the radiological level. Both administered medicines had similar regeneration effects. Pak J Physiol 2022;18(3):19–22